2019
DOI: 10.1108/rsr-12-2018-0075
|View full text |Cite
|
Sign up to set email alerts
|

Unique or ubiquitous: information literacy instruction outside academia

Abstract: Purpose: To investigate how U.S. public libraries offer information literacy (IL) instruction to their patrons. Design/methodology: A content analysis of eight library websites to determine 1) passive information literacy instruction and 2) active literacy instruction. Results: Library web guides offer passive information literacy instruction by highlighting resources patrons may wish to access to resolve information inquiries. Further, we found that a little less than 50% of library programming offers some IL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 19 publications
0
7
0
1
Order By: Relevance
“…Some of the international studies have investigated information literacy in public libraries (e.g. Harding, 2008;Ireland, 2017;Jacobsen, 2017;Julien and Hoffman, 2008;Kingori et al, 2016;Matteson and Gersch, 2019;Nielsen and Borlund, 2011;Widdowson and Smart, 2013). The results of these studies revealed that some public libraries offered information literacy instruction and the users of these libraries participated in the programmes offered for their information needs.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the international studies have investigated information literacy in public libraries (e.g. Harding, 2008;Ireland, 2017;Jacobsen, 2017;Julien and Hoffman, 2008;Kingori et al, 2016;Matteson and Gersch, 2019;Nielsen and Borlund, 2011;Widdowson and Smart, 2013). The results of these studies revealed that some public libraries offered information literacy instruction and the users of these libraries participated in the programmes offered for their information needs.…”
Section: Introductionmentioning
confidence: 99%
“…This is the reason why researches on fake news and publications mainly concentrate on inaccurate or deceptive information being spread through multiple social media platforms and news feeds. They demonstrate methods in the battle against fake news via media literacy course (Matteson and Gersch, 2019;Hanz and Kingsland, 2020). Recent research conducted by some researchers (Ottonicar et al, 2021) reveals urgency of fake news in 2018.…”
Section: Literature Reviewmentioning
confidence: 98%
“…Much has been written about information literacy. Researchers outline specialized modules, courses and seminars on information literacy teaching methods both in colleges and higher educational institutions (Whiley et al, 2017;Vasilyeva and Vasilyeva, 2019;Seng, Carlon and Cross, 2020) and public libraries (Matteson and Gersch, 2019). It is mostly librarians who organize those courses and seminars since information resources in their traditional, paper and electronic format are accumulated in libraries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Public libraries also offer IL instruction through classes on topics of interest to patrons such as detecting fake news, financial literacy, or even managing a fantasy football team (Ireland, 2017;Jacobsen, 2017). In a preliminary project to the research we are reporting here, we examined eight public library websites to determine what kind of IL instruction might be occurring through their programming and through content on their website (Matteson & Gersch, 2019). We found that all but one of the library websites offered passive IL instruction through subject guides available on a variety of topics.…”
Section: Examples Of Il Instruction In Public Librariesmentioning
confidence: 99%